Sodium-ion battery hard carbon negative electrode material with open microporous structure and preparation method of sodium-ion battery hard carbon negative electrode material

By introducing an open microporous structure into the hard carbon anode material of sodium ion batteries, the problem of limited diffusion of sodium ion ions in existing materials is solved, and the rate performance and stability are significantly improved, providing new possibilities for the development of sodium ion battery technology.

CN119517982APending Publication Date: 2025-02-25INST OF PHYSICS HENAN ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411698485.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The microporous structures of existing sodium ion battery hard carbon anode materials are mostly closed, which makes it difficult for sodium ions to diffuse quickly during charging and discharging, affecting rate performance and energy density. The preparation methods of existing materials have failed to effectively develop open microporous structures.

Method used

A hard carbon negative electrode material with an open microporous structure is adopted, which is composed of a large number of turbine-shaped microcrystals. Through a specific preparation method, including heating silicon oil in a specific gas atmosphere, forming a silicon oxide carbon composite material, and forming a hard carbon negative electrode material with an open microporous structure through steps such as etching and high-temperature annealing.

Benefits of technology

The diffusion rate of sodium ions is significantly improved, the rate performance is enhanced, and the stability of the material and the service life of the battery are improved by optimizing the micropore structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517982A_ABST
    Figure CN119517982A_ABST
Patent Text Reader

Abstract

The invention provides a sodium-ion battery hard carbon negative electrode material with an open microporous structure and a preparation method thereof, and the specific preparation process comprises the following steps: (1) carrying out high-temperature pyrolysis on silicone oil to obtain a silicon-oxygen-carbon composite material; (2) etching the silicon-oxygen-carbon composite material prepared in the step (1) to remove silicon-oxygen components in the silicon-oxygen-carbon composite material; and (3) carrying out high-temperature annealing treatment on the etched material to finally obtain the hard carbon negative electrode material. The hard carbon negative electrode material prepared by the invention is composed of a large number of turbine-shaped microcrystals, and the whole hard carbon negative electrode material is in a spherical shape and shows a typical open-type microporous structure. The open micropore structure can effectively promote sodium ion transmission, the rate capability of the hard carbon negative electrode is remarkably improved, and the hard carbon negative electrode has high specific capacity, high initial coulombic efficiency and good cycling stability. In addition, the preparation implementation process is relatively simple, and industrial production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium ion batteries, and more specifically, to a sodium ion battery hard carbon negative electrode material with an open microporous structure and a preparation method thereof. Background Art

[0002] As a potential energy storage technology, sodium-ion batteries have received extensive attention in recent years, especially in the fields of electric vehicles and renewable energy storage. Compared with lithium-ion batteries, sodium-ion batteries have the advantages of abundant sodium resources and low cost, which makes them show good prospects in large-scale energy storage applications. However, the performance of sodium-ion batteries depends largely on the selection and design of negative electrode materials. At present, hard carbon materials are considered to be the most promising candidate materials for the negative electrode of sodium-ion batteries. Hard carbon has high theoretical specific capacity, good cycle stability and low cost, so it has attracted widespread attention from researchers. Existing hard carbon materials are mostly derived from biomass, polymers and coke, etc., and are obtained through appropriate pyrolysis or chemical treatment.

[0003] A major problem with existing hard carbon negative electrode materials is the closed nature of their microporous structure. Most of the pores formed in the preparation process of hard carbon materials are closed, which makes it difficult for sodium ions to diffuse quickly during the charge and discharge process, affecting the rate performance and energy density of the battery. This closed microporous structure restricts the migration of sodium ions in the electrode material, which in turn causes sodium ion retention during the charge and discharge process, seriously affecting the cycle stability and service life of the battery. In addition, there are various preparation methods for existing hard carbon materials, but most methods fail to effectively develop and design microporous structures with practical application value. In addition, some studies have focused on improving the specific capacity of hard carbon negative electrode materials, while ignoring the effect of microporous structure on ion diffusion. This one-sided pursuit of capacity in research has resulted in many hard carbon negative electrode materials performing poorly in practical applications.

[0004] The hard carbon structure design with an open microporous structure can not only solve the retention problem of sodium ions during the charging and discharging process, but also increase the specific surface area of ​​the material, provide more sodium ions with embedding and de-embedding sites, and thus improve the energy density and power performance of the battery. In addition, the optimized microporous structure can also help improve the stability of the material and extend the service life of the battery. Therefore, the development of a sodium ion battery hard carbon negative electrode material with an open microporous structure can effectively solve the shortcomings of existing materials and provide new possibilities for the development of sodium ion battery technology. This innovation not only helps to promote the performance of sodium ion batteries, but also lays the foundation for its application in future electric vehicles, renewable energy storage and other fields. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problem of poor rate performance of hard carbon negative electrode of sodium ion battery in the prior art, and propose a sodium ion battery hard carbon negative electrode material with an open microporous structure, and provide a preparation method of the hard carbon negative electrode material.

[0006] Technical principle of the present invention:

[0007] The hard carbon negative electrode material for a sodium ion battery with an open microporous structure of the present invention not only solves the retention problem of sodium ions during the charging and discharging process, ensures the rapid diffusion of sodium ions during the charging and discharging process, but also provides more sodium ions with embedding and de-embedding sites, thus giving the hard carbon negative electrode material a strong rate capability.

[0008] In order to achieve the above-mentioned purpose of the invention, the present invention has developed the following technical solutions:

[0009] A sodium ion battery hard carbon negative electrode material with an open microporous structure, which is composed of a large number of turbine-shaped microcrystals, has an overall spherical morphology, and exhibits a typical open microporous structure.

[0010] Preferably, the hard carbon negative electrode material has a size of 10 nm to 50 μm.

[0011] Preferably, the size of the micropores in the hard carbon negative electrode material is 0.3 nm to 2 nm.

[0012] The present invention also provides a method for preparing the above-mentioned sodium ion battery hard carbon negative electrode material with an open microporous structure, comprising the following steps:

[0013] S1: Connect the specific gas storage device to one end of the controllable heating device, the other end of the controllable heating device is connected to the inlet of the reaction furnace, and the controllable heating device is filled with silicone oil;

[0014] S2: heating the reactor at a certain heating rate in a specific gas atmosphere;

[0015] S3: Adjust the temperature of the controllable heating device to heat the silicone oil to a certain temperature to obtain its vapor, and introduce it into the reaction furnace using a specific gas.

[0016] S4: maintaining the temperature of the reactor under this condition for 1h-10h, and then stopping the introduction of silicone oil vapor;

[0017] S5: naturally cooling the reaction furnace to room temperature in a specific gas atmosphere to obtain a silicon-oxygen-carbon composite material;

[0018] S6: stirring the silicon-oxygen-carbon composite material obtained in S5 in a 5% concentration etching solution for 12 hours, and then repeatedly filtering it with deionized water to obtain a sample;

[0019] S7: After drying the sample obtained in S6, place it in a high-temperature carbonization furnace, heat the carbonization furnace to a corresponding temperature at a certain heating rate in an inert gas atmosphere, keep it warm for a certain period of time, perform high-temperature annealing, and finally naturally cool the carbonization furnace to room temperature to obtain a hard carbon negative electrode material.

[0020] Preferably, the silicone oil is one or more of dimethylsiloxane, diethyldiethoxysilane, trimethylchlorosilane, octamethyltrisiloxane, cyclopentasiloxane, octamethylcyclotetrasiloxane, hexamethyldisilane, and octamethyltrisiloxane.

[0021] Preferably, the specific gas is one or more of argon, nitrogen, carbon monoxide, carbon dioxide, nitric oxide and water vapor.

[0022] Preferably, the heating rate of the reaction furnace in S2 is 2-10°C / min, and the heating temperature is 800°C to 1200°C.

[0023] Preferably, the temperature of the heating device in S3 is 25°C to 350°C.

[0024] Preferably, the etching solution in S6 is one or more of hydrofluoric acid, sodium hydroxide, ammonia water and potassium hydroxide.

[0025] Preferably, the inert gas in S7 is argon or nitrogen, the carbonization furnace heating rate is 1°C / min to 10°C / min; the carbonization furnace heating temperature is 1100°C to 2000°C; and the insulation time is 0.5-8h.

[0026] Compared with the prior art, this patent has the following beneficial effects:

[0027] 1. The present invention introduces an open microporous structure into the hard carbon negative electrode material for sodium ion batteries, which can significantly increase the sodium ion diffusion rate, thereby enhancing its rate performance. In addition, the preparation process is relatively simple and efficient, and is suitable for large-scale production.

[0028] 2. Silicone oil is cheap and easy to obtain, and is suitable for large-scale production. The prepared silicon-oxygen-carbon composite material is etched to remove the silicon-oxygen components. The space originally occupied by the silicon-oxygen components in the composite material forms a microporous structure, which effectively shortens the sodium ion transmission path and gives the hard carbon material a large number of active sites, thereby significantly promoting the transmission and storage of sodium ions; high-temperature annealing can remove the remaining carbon components in the composite material and form a carbon microcrystalline structure with a large interlayer spacing suitable for sodium ion storage, and finally obtain a hard carbon negative electrode material; this method has a simple process and a high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is a SEM morphology image of the silicon-oxygen-carbon composite material obtained by pyrolyzing silicone oil in Example 1;

[0031] Figure 2 This is a SEM morphology image of the silicon-oxygen-carbon composite material after etching in Example 1;

[0032] Figure 3 This is an EDS image of the silicon-oxygen-carbon composite material after etching in Example 1;

[0033] Figure 4 TEM image of the hard carbon negative electrode material in Example 1;

[0034] Figure 5 is a pore size distribution diagram of the hard carbon negative electrode material in Example 1;

[0035] Figure 6 is the XRD spectrum of the hard carbon negative electrode material in Example 1;

[0036] Figure 7 This is the first charge and discharge curve of the hard carbon negative electrode material in Example 1;

[0037] Figure 8 The cycle performance of the hard carbon negative electrode material in Example 1;

[0038] Fig. 9 This is the rate performance of the hard carbon negative electrode material in Example 1. DETAILED DESCRIPTION

[0039] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0040] Example 1

[0041] A method for preparing the above-mentioned sodium ion battery hard carbon negative electrode material with an open microporous structure comprises the following steps:

[0042] S1: connecting an argon storage device to one end of a controllable heating device, the other end of the controllable heating device is connected to the inlet of a reaction furnace, and the controllable heating device is filled with diethyldiethoxysilane;

[0043] S2: The temperature of the reaction furnace was raised to 800° C. at a heating rate of 5° C. / min in an argon atmosphere.

[0044] S3: adjusting the temperature of the controllable heating device to 130° C., heating diethyldiethoxysilane to obtain its vapor, and introducing it into the reaction furnace using argon gas; controlling the amount of diethyldiethoxysilane vapor introduced into the reaction furnace by switching valves and flow meters;

[0045] S4: maintaining the temperature of the reaction furnace under this condition for 1 hour, and then stopping the introduction of diethyldiethoxysilane vapor;

[0046] S5: Cooling the reaction furnace naturally to room temperature in an argon atmosphere to obtain a silicon-oxygen-carbon composite material; Figure 1 shown.

[0047] S6: stirring the silicon-oxygen-carbon composite material obtained in S5 in a 5% concentration hydrofluoric acid solution for 12 hours, and then repeatedly filtering it with deionized water to obtain a sample;

[0048] S7: The sample prepared in S6 is dried and placed in a high-temperature carbonization furnace. The carbonization furnace is heated to 1200°C at a heating rate of 2°C / min in an argon atmosphere, and kept at this temperature for 8 hours for high-temperature annealing. Finally, the carbonization furnace is naturally cooled to room temperature to obtain a hard carbon negative electrode material; Figure 2 and Figure 3 shown.

[0049] Figure 4 The TEM image of the obtained hard carbon negative electrode material shows that the hard carbon negative electrode material is composed of a large number of turbine-shaped carbon microcrystals. Figure 5 It can be confirmed from the pore size distribution diagram that after etching, there are a large number of micropores in the hard carbon negative electrode material, and the pore size is about 0.7nm. Figure 6 This is the XRD spectrum of the obtained hard carbon negative electrode material, from which the peak corresponding to the (002) crystal plane of the carbon microcrystal can be clearly seen. According to the Bragg equation, the interplanar spacing is calculated to be about 0.38 nm. Figure 7 The first charge and discharge curve of the obtained hard carbon negative electrode material at 0.1C shows that the first charge capacity of the hard carbon negative electrode is 303.6 mAh / g and the first coulombic efficiency is 83%. In the subsequent 100 cycles, the hard carbon negative electrode showed no obvious capacity loss, such as Figure 8 shown. Fig. 9This is the rate performance of the hard carbon negative electrode. At 0.1, 0.5, 1, 2 and 3C, the specific capacities of the hard carbon negative electrode are 303.2, 251.4, 191.7, 149.0 and 94.3 mAh / g, respectively.

[0050] Example 2

[0051] A method for preparing the above-mentioned sodium ion battery hard carbon negative electrode material with an open microporous structure comprises the following steps:

[0052] S1: connecting an argon storage device to one end of a controllable heating device, the other end of the controllable heating device is connected to the inlet of a reaction furnace, and the controllable heating device is filled with cyclopentasiloxane;

[0053] S2: The temperature of the reaction furnace was raised to 1200° C. at a heating rate of 10° C. / min in an argon atmosphere.

[0054] S3: adjusting the temperature of the controllable heating device to 200° C., heating cyclopentasiloxane to obtain its vapor, and introducing it into the reaction furnace using argon gas; controlling the amount of cyclopentasiloxane vapor introduced into the reaction furnace by switching valves and flow meters;

[0055] S4: maintaining the temperature of the reaction furnace under this condition for 10 hours, and then stopping the introduction of cyclopentasiloxane vapor;

[0056] S5: The reaction furnace is naturally cooled to room temperature in an argon atmosphere to obtain a silicon-oxygen-carbon composite material.

[0057] S6: stirring the silicon-oxygen-carbon composite material obtained in S5 in a 5% sodium hydroxide solution for 12 hours, and then repeatedly filtering it with deionized water to obtain a sample;

[0058] S7: The sample prepared in S6 was dried and placed in a high-temperature carbonization furnace. The carbonization furnace was heated to 1200°C at a heating rate of 10°C / min in an argon atmosphere, and kept warm for 5 hours for high-temperature annealing. Finally, the carbonization furnace was naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0059] At 0.1C, the first charge capacity of the hard carbon negative electrode was 280.2 mAh / g, and the first coulombic efficiency was 79%. In the subsequent 100 cycles, the hard carbon negative electrode showed no obvious capacity loss. In addition, at 0.1, 0.5, 1, 2 and 3C, the specific capacity of the hard carbon negative electrode was 280.5, 243.6, 173.1, 122.7 and 74.1 mAh / g, respectively.

[0060] Example 3

[0061] A method for preparing the above-mentioned sodium ion battery hard carbon negative electrode material with an open microporous structure comprises the following steps:

[0062] S1: connecting an argon storage device to one end of a controllable heating device, the other end of the controllable heating device is connected to the inlet of a reaction furnace, and the controllable heating device is filled with hexamethyldisilane;

[0063] S2: The temperature of the reaction furnace was raised to 1100° C. at a heating rate of 10° C. / min in an argon atmosphere.

[0064] S3: adjusting the temperature of the controllable heating device to 200° C., heating hexamethyldisilane to obtain its vapor, and introducing it into the reaction furnace using argon gas; controlling the amount of hexamethyldisilane vapor introduced into the reaction furnace by switching valves and flow meters;

[0065] S4: maintaining the temperature of the reactor under this condition for 5 hours, then stopping the introduction of hexamethyldisilane vapor;

[0066] S5: The reaction furnace is naturally cooled to room temperature in an argon atmosphere to obtain a silicon-oxygen-carbon composite material.

[0067] S6: stirring the silicon-oxygen-carbon composite material obtained in S5 in a 5% sodium hydroxide solution for 12 hours, and then repeatedly filtering it with deionized water to obtain a sample;

[0068] S7: The sample prepared in S6 was dried and placed in a high-temperature carbonization furnace. The carbonization furnace was heated to 1500°C at a heating rate of 10°C / min in an argon atmosphere, and kept warm for 3 hours for high-temperature annealing. Finally, the carbonization furnace was naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0069] At 0.1C, the first charge capacity of the hard carbon negative electrode was 290.5 mAh / g, and the first coulombic efficiency was 80%. In the subsequent 100 cycles, the hard carbon negative electrode showed no obvious capacity loss. In addition, at 0.1, 0.5, 1, 2 and 3C, the specific capacities of the hard carbon negative electrode were 290.2, 240.6, 179.7, 140.3 and 86.2 mAh / g, respectively.

[0070] Example 4

[0071] A method for preparing the above-mentioned sodium ion battery hard carbon negative electrode material with an open microporous structure comprises the following steps:

[0072] S1: connecting an argon storage device to one end of a controllable heating device, the other end of the controllable heating device is connected to the inlet of a reaction furnace, and trimethylchlorosilane is contained in the controllable heating device;

[0073] S2: The temperature of the reaction furnace was raised to 1000° C. at a heating rate of 10° C. / min in an argon atmosphere.

[0074] S3: adjusting the temperature of the controllable heating device to 50° C., heating trimethylchlorosilane to obtain its vapor, and introducing it into the reaction furnace using argon gas; controlling the amount of trimethylchlorosilane vapor introduced into the reaction furnace by switching valves and flow meters;

[0075] S4: maintaining the temperature of the reactor under this condition for 5 hours, and then stopping the introduction of trimethylsilyl chloride vapor;

[0076] S5: The reaction furnace is naturally cooled to room temperature in an argon atmosphere to obtain a silicon-oxygen-carbon composite material.

[0077] S6: stirring the silicon-oxygen-carbon composite material obtained in S5 in a 5% concentration hydrofluoric acid solution for 12 hours, and then repeatedly filtering it with deionized water to obtain a sample;

[0078] S7: The sample prepared in S6 was dried and placed in a high-temperature carbonization furnace. The carbonization furnace was heated to 1700°C at a heating rate of 10°C / min in a nitrogen atmosphere. The temperature was kept at this temperature for 10 hours for high-temperature annealing. Finally, the carbonization furnace was naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0079] At 0.1C, the first charge capacity of the hard carbon negative electrode was 283.5 mAh / g, and the first coulombic efficiency was 78%. In the subsequent 100 cycles, the hard carbon negative electrode showed no obvious capacity loss. In addition, at 0.1, 0.5, 1, 2 and 3C, the specific capacity of the hard carbon negative electrode was 283.5, 245.2, 171.6, 125.3 and 78.5 mAh / g, respectively.

[0080] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A sodium ion battery hard carbon negative electrode material with an open microporous structure, characterized in that: The hard carbon negative electrode material is composed of a large number of turbine-shaped microcrystals, has an overall spherical morphology, and exhibits a typical open microporous structure.

2. The hard carbon negative electrode material according to claim 1, characterized in that: The hard carbon negative electrode material has a size of 10 nm to 50 μm.

3. The hard carbon negative electrode material according to claim 1, characterized in that: The micropore size in the hard carbon negative electrode material is 0.3nm to 2nm.

4. A method for preparing a sodium ion battery hard carbon negative electrode material having an open microporous structure according to any one of claims 1 to 3, characterized in that: The steps include: S1: Connect the specific gas storage device to one end of the controllable heating device, the other end of the controllable heating device is connected to the inlet of the reaction furnace, and the controllable heating device is filled with silicone oil; S2: heating the reactor at a certain heating rate in a specific gas atmosphere; S3: Adjust the temperature of the controllable heating device to heat the silicone oil to a certain temperature to obtain its vapor, and introduce it into the reaction furnace using a specific gas. S4: maintaining the temperature of the reactor under this condition for 1h-10h, and then stopping the introduction of silicone oil vapor; S5: naturally cooling the reaction furnace to room temperature in a specific gas atmosphere to obtain a silicon-oxygen-carbon composite material; S6: stirring the silicon-oxygen-carbon composite material obtained in S5 in a 5% concentration etching solution for 12 hours, and then repeatedly filtering it with deionized water to obtain a sample; S7: After drying the sample obtained in S6, place it in a high-temperature carbonization furnace, heat the carbonization furnace to a corresponding temperature at a certain heating rate in an inert gas atmosphere, keep it warm for a certain period of time, perform high-temperature annealing, and finally naturally cool the carbonization furnace to room temperature to obtain a hard carbon negative electrode material.